Questioning the Harmonization of Basic Legal Values in the Diorama of Indonesia's State of Law Thought - Bambang Tri Bawono (Faculty of Law, Universitas Pekalongan, 2021)
Radbruch has long discovered three basic values in law, namely the values of justice, expediency, and certainty in law, however, Radbruch has not yet explained the applicability of these three values within the framework of a harmonious system, this in its development has resulted in spannungsverhaltnis between these three values. This paper, which uses a sociological and philosophical juridical method, tries to explain the disharmony of the three basic values of Radbruch's law. Based on various existing studies, it can be seen that Radbruch only divides the three basic legal values partially, not as a unit as a sub-system, therefore the ecosystem in law which is based on Radbruch's three basic values experiences distortion, problems of distortion or spannungsverhaltnis between the three values. This basis can be avoided by creating harmony between these basic legal values through an ecosystem of interrelated legal basic values as a holistic integrated system.